From One Library to Another: the New Robert de Sorbon Library of the University of Reims - Bekri-Dinoird, Carine El (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
The new Robert de Sorbon library opened its doors in September 2006. The county of Champagne Ardenne managed the planning of the new building. The project focused on a totally new way of running this library and affirmed its structural role on the campus. The ambition was to make the future library the reference centre of the university and a real support to education and research. This library is also one of the first libraries in France to adopt high environmental quality as a global approach.